Delimitação de rede de drenagem e limite de bacia hidrográfica utilizando sistema de informações geográficas: aplicação no rio Maranguapinho - Ceará - Albuquerque, Adrya Santos (2017)
Based on the need to manage water resources, a precise delimitation of the river basin is necessary, since this is a planning unit. With the increasing development of Information Technology, it became possible to use geographical information systems (GIS) in the delimitation of basins. In this sense, the present study aims to present the methodology of automatic delimitation of basins adopted by a plugin added to the UFC System and apply it to a case study in the Maranguapinho River. To perform the delimitation, we used the land elevation data from the Brazilian Geomorphometric Database, Topodata, and the ottocoded hydrographic base (BHO) used by ANA. Rainfall data from ANA were also used, providing a basis for future hydrological studies in the basin. We used the ArcGIS 10.2.2 GIS. As a result, software obtained the digital elevation model, the drainage network and the watershed dividers, the contours, the pluviometric stations with their influence areas in the basin and the main river path. The use of the plugin was advantageous when compared to the delimitation from the tools of ArcGIS, presenting less data processing time. In addition, it allowed the standardization in the delimitation of basins, reducing the errors of human interpretation.